The Shariah Audit Framework from Practitioners’ Perspective: A Mirage or Fact? - Noor Aimi Mohamad Puad; Nurdianawati Irwani Abdullah; Zurina Shafii (Universiti Sains Islam Malaysia, 2024)
The positive development of Islamic financial system nowadays leads to the growth of products and services offered by Islamic financial institutions. However, some of them may have overlooked certain aspects that could affect Shariah-compliancy of the products and services. The occurrence of Shariah non-compliance risk may would adversely affect the reputation of Islamic finance and the confidence of market participants among depositors and investors. This scenario calls for a systematic check-and-balance functions within the institution. Shariah auditor being one of the components of Shariah governance plays an important role in ensuring the effectiveness of internal control system for Shariah compliance. Prior research reveals that the standard Shariah audit framework has not been developed yet; thus, the present practice is carried out by the internal institutional effort which heavily relies on the conventional audit system. The aim of this study is to explore the relevancy of Shariah audit framework from the eyes of practitioners of various Islamic financial institutions; whether it is a new innovative discipline or merely replicating the conventional audit structure. Ten semi-structured interviews were conducted involving selected auditors, Shariah compliance officers and Shariah committee members. Thematic analyses were adopted to analyze the data. It can be deduced that there is a need for a specific Shariah audit framework as a benchmark but with certain requirements and limitations. This study may provide relevant guidelines especially for policymaker in developing a standardized specific framework for Shariah audit.